FEATURES OF CONSUMER BEHAVIOR WHEN BUYING SOCIALLY IMPORTANT GOODS - Yampolskaya, D. (Journal of Economic Research & Business Administration, 2019)
The place of a person in a particular society is largely defined by what and how they purchase. This process is easily perceived by the reference group. Social group determines the motivation of a young person when they buy some kinds of goods. In this regard, a problem of social audience management through specific consumption and purchase models arises. The aim of the present study is modeling the purchasing process of goods that have a certain social status on the youth market: mobile phones (smartphones) and fitness bracelet (trackers). The object of study is the young audience; the subjects are the motives and determinants of consumer behavior during decision-making, and the principles of demand formation. Students of the Economics Faculty of the Peoples’ Friendship University of Russia (RUDN), Moscow, conducted the study of consumer behavior in April-May 2018. In-depth interviews and questionnaires were used as methods of research. The following models of the consumer behavior processes were used: Stimulus-Organism-Response Model of Decision Making, the Foote, Cone and Belding Model, the Howard-Sheth model, and O’Shaughnessy studies. The results of the modeling process are the basis for creating marketing communication with consumers on a commercial basis and may be of interest to manufacturers and sellers of this type of products in Russia.